Majelis Ta’lim sebagai Model Pendidikan Non Formal Islam - Zuhri Zuhri (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2019)
The article wants to discuss the existence of the majelis ta'lim as one model of Islamic non-formal education. The discussion uses a qualitative descriptive method by examining library sources and supported by field data. The results of the discussion show that majelis ta’lim is one of non formal Islamic Education system, majelis ta’lim has role and function that is very important in growing and developing of Islamic education. The implementation of this education can help to understand the developing process in religious and community life for members of majelis ta’lim. Now a days, function and role of majelis ta’lim is reducted, so that lack and not optimal for the people. Generally majelis ta’lim is held potluck, as decitation group, the recitation that was held by muslim especially female voluntarily, and without preparation.